A novel flow cytometry single tube bead assay for quantitation of von Willebrand factor antigen and collagen-binding - Mina, Ashraf; Favaloro, Emmanuel J.; Koutts, Jerry (Thrombosis and Haemostasis, 2012)
Deficiency of or defects in the plasma protein von Willebrand factor (VWF) lead to bleeding and von Willebrand disease (VWD), which may be congenital or acquired. VWD is considered the most common inherited bleeding disorder and laboratory testing for VWF level and activity is critical for appropriate diagnosis and management. We have designed and established a novel Flow Cytometry (FC) based method for measuring VWF antigen (VWF:Ag) and collagen binding (VWF:CB), together in the same tube and at the same time. The results of the novel FC method have been compared against existing reference methods using a range of normal and pathological material. Methods correlated well (VWF:Ag, r=0.866; VWF:CB, r=0.888) and generally permitted similar discrimination of quantitative versus qualitative VWD types (e.g. type 1 vs type 2A or 2B VWD). The novel procedure is expected to permit future streamlined performance of VWD screening, either using stand-alone FC systems or potentially incorporated into FC-capable automated blood cell and particle counters to allow for improved, automated and faster identification or exclusion of VWD.
Keywords: Von Willebrand factor; von Willebrand disease; VWF; VWD; collagen binding